Peer review for handoff education in a transition to residency course: A prospective cohort study - Rajiv Trehan; Catherine Chen; Raman Bhalla (Health Science Reports, 2024)
Abstract Background and Aims Association of American Medical Colleges (AAMC) and Accreditation Council for Graduate Medical Education (ACGME) mandate training in handoff delivery for students and residents. Communication errors, including errors during handoffs of patient care, account for over 2/3 of sentinel events. This study aims to assess the effectiveness of peer‐assisted learning (PAL) in handoff education within a longitudinal framework. Methods This study involved the analysis of fourth‐year medical students (n = 67) enrolled in a transition to residency program designed to reinforce skills essential for success in internal medicine residencies. We modified the I‐PASS handoff rubric for a single‐encounter evaluation. Before attending the transitions of care workshop, students submitted one written handoff report. During high‐fidelity simulation sessions, peers evaluated the written document as well as verbal handoffs, while faculty evaluated a recorded verbal version. The primary outcome measured was improvement in handoff quality and accuracy over time and secondary outcomes compared peer‐ and self‐evaluations to faculty assessments. Results Overall, students demonstrated a statistically significant improvement in handoff quality and accuracy across all scoring criteria after completing the peer evaluation process. Peer evaluations did not demonstrate statistically significant differences in scores for quality or accuracy questions as compared to faculty. Conclusion Peer evaluators effectively assessed handoff reports using the modified I‐PASS checklist yielding outcomes similar to faculty while providing feedback. These findings provide exciting evidence that should prompt training programs to consider incorporating standardized peer review into handoff education for medical students and, potentially, residents. The detailed evaluation of individual handoff events fosters feedback skills essential for ongoing professional growth and clinical excellence.